Pengaruh Disiplin Kerja dan Stres Kerja terhadap Kinerja Karyawan pada PT Timah TBK Perwakilan Jakarta - Odeta Levin; H. Tjeri Hadjrillah (Global Leadership Organizational Research in Management, 2024)
This study aims to determine the effect of work discipline and work stress on employee performance at PT Timah Tbk Representative Jakarta. The method used in this study is quantitative. The sampling using saturated samples with a total sample of 75 people. Research Data obtained by distributing questionnaires. Data analysis used is validity test, reliability test, classical assumption test, multiple linear regression, coefficient of determination and hypothesis test. The results showed that the value of the coefficient of determination obtained by 0.546 or 54.6% and the rest is influenced by other factors that were not studied. Partial testing (t test) of work discipline on employee performance found the results of t-count > t-Table is equal to 6.051 > 1.993 with a sig value of 0.000 < 0.05. While the work stress on the performance of employees found the results of t-count > t-table is equal to 3.383 > 1.993 with a sig value of 0.001 < 0.05. Based on these results, both the first hypothesis and the second hypothesis explain partially that each variable is proven to have a significant effect on the dependent variable. Simultaneous hypothesis testing (test F) found the results of F-count > F-table is equal to 43.320 > 3.124 with a sig value of 0.000 < 0.05. Thus Ho is rejected and Ha is accepted. The multiple linear regression analysis found the value of the equation Y = 11.416 + 0.438 X1 + 0.270 X2. Based on these results, it means that work discipline and work stress have a positive and significant effect on employee performance at PT Timah Tbk, representative of Jakarta